Answer:
![a + b + c = \pi \\ = > c= \pi - a - b \\ < = > \tan(c) = \tan(\pi - a - b) = -\tan(a + b)](https://tex.z-dn.net/?f=a%20%2B%20b%20%2B%20c%20%3D%20%5Cpi%20%5C%5C%20%20%3D%20%20%3E%20c%3D%20%20%5Cpi%20-%20a%20-%20b%20%5C%5C%20%20%3C%20%20%3D%20%20%3E%20%20%5Ctan%28c%29%20%20%3D%20%20%5Ctan%28%5Cpi%20-%20a%20-%20b%29%20%20%3D%20%20-%5Ctan%28a%20%2B%20b%29%20)
Step-by-step explanation:
we have:
![\tan(a) + \tan(b) + \tan(c) \\ = \tan(a) + \tan(b) - \tan(a + b) \\ = \tan( a) + \tan(b) - \frac{ \tan(a) + \tan(b) }{1 - \tan(a) \tan(b) } \\ = \frac{ ( \tan(a) + \tan(b) ) \tan(a) \tan(b) }{ \tan(a) \tan(b) - 1 } (1)](https://tex.z-dn.net/?f=%20%5Ctan%28a%29%20%20%2B%20%20%5Ctan%28b%29%20%20%2B%20%20%5Ctan%28c%29%20%20%5C%5C%20%20%3D%20%20%5Ctan%28a%29%20%20%2B%20%20%5Ctan%28b%29%20%20-%20%20%5Ctan%28a%20%2B%20b%29%20%20%5C%5C%20%20%3D%20%20%5Ctan%28%20a%29%20%20%2B%20%20%5Ctan%28b%29%20%20-%20%20%5Cfrac%7B%20%5Ctan%28a%29%20%2B%20%20%5Ctan%28b%29%20%20%7D%7B1%20-%20%20%5Ctan%28a%29%20%20%5Ctan%28b%29%20%7D%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7B%20%28%20%5Ctan%28a%29%20%2B%20%20%5Ctan%28b%29%20%20%29%20%5Ctan%28a%29%20%5Ctan%28b%29%20%20%7D%7B%20%5Ctan%28a%29%20%5Ctan%28b%29%20%20-%201%20%7D%20%281%29)
we also have:
![\tan(a) \tan(b) \tan(c) \\ = - \tan(a) \tan(b) \tan(a + b) \\ = \frac{ -(\tan( a ) + \tan(b) ) \tan(a) \tan(b) }{1 - \tan(a) \tan(b) } \\ = \frac{( \tan(a) + \tan(b)) \tan(a) \tan(b) }{ \tan(a) \tan(b) - 1 } (2)](https://tex.z-dn.net/?f=%20%5Ctan%28a%29%20%20%5Ctan%28b%29%20%20%5Ctan%28c%29%20%20%5C%5C%20%20%3D%20%20-%20%20%5Ctan%28a%29%20%20%5Ctan%28b%29%20%20%5Ctan%28a%20%2B%20b%29%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7B%20-%28%5Ctan%28%20a%20%20%29%20%20%20%2B%20%5Ctan%28b%29%20%29%20%5Ctan%28a%29%20%20%5Ctan%28b%29%20%7D%7B1%20-%20%20%5Ctan%28a%29%20%20%5Ctan%28b%29%20%7D%20%20%5C%5C%20%20%3D%20%20%5Cfrac%7B%28%20%5Ctan%28a%29%20%20%2B%20%20%5Ctan%28b%29%29%20%5Ctan%28a%29%20%20%20%5Ctan%28b%29%20%7D%7B%20%5Ctan%28a%29%20%5Ctan%28b%29%20%20-%201%20%7D%20%282%29)
from (1)(2) => proven
Answer:
Maggie is 13 years old.
Step-by-step explanation:
The explanation is attached.
Answer: 918km^2
Step-by-step explanation:
![area(a): 1700km^2\\percentage(p): 5.75 = \frac{5.75}{100}=0.0575\\years(y): 8](https://tex.z-dn.net/?f=area%28a%29%3A%201700km%5E2%5C%5Cpercentage%28p%29%3A%205.75%20%3D%20%5Cfrac%7B5.75%7D%7B100%7D%3D0.0575%5C%5Cyears%28y%29%3A%208)
Let x be the new dimension of the area;
![x=a-(a*p*y)](https://tex.z-dn.net/?f=x%3Da-%28a%2Ap%2Ay%29)
![x=(1700km^2)-(1700km^2*0.0575*8)\\x=1700km^2-782km^2\\x=918km^2](https://tex.z-dn.net/?f=x%3D%281700km%5E2%29-%281700km%5E2%2A0.0575%2A8%29%5C%5Cx%3D1700km%5E2-782km%5E2%5C%5Cx%3D918km%5E2)
Set up a ratio:
1/50 = x/480
Cross multiply:
50x = 480
Divide both sides by 50:
X = 9.6
The distance on the map is 9.6 cm
Answer:
The leading coefficient of the polynomial is -9.
Step-by-step explanation:
9 is the leading coefficient of this polynomial because if you rearrange the exponents from greatest to least, you will get this :
-9x3 + 5x2 + 7x -10
Your leading coefficient is the number included with your degree or highest exponent.